A new late Neanderthal from Crimea reveals long-distance connections across Eurasia - Emily M. Pigott; Konstantina Cheshmedzhieva; Elke Zeller; Laura G. Van der Sluis; Manasij Pal Chowdhury; Maddalena Giannì; Emese Végh; Thorsten Uthmeier; Victor Chabai; Marylène Patou-Mathis; Petra G. Šimková; Jana N. Voglmayr; et al. (Proceedings of the National Academy of Sciences, 2025)
The Crimean Peninsula contains several important Middle and Upper Paleolithic sites, including Starosele, Kabazi II, and Siuren I. The region has been considered a potential refugium for Neanderthals before their replacement by Homo sapiens . However, no genetic data have been obtained from any of these late Neanderthals, some being inaccessible or badly preserved. Starosele is a notable site which has undergone excavations in recent years. We used collagen peptide mass fingerprinting (Zooarchaeology by Mass Spectrometry, ZooMS), to screen for potential human remains among thousands of fragmented bones from the site. Of the 150 bone fragments we analyzed, 97.3% had sufficient collagen preservation for taxonomic identification. Our results suggest Paleolithic humans primarily hunted horses. One ~5 cm bone fragment yielded peptide mass fingerprints matching Hominidae . Radiocarbon dating revealed an age range of 46 to 45,000 y old, close to the transition from the disappearance of Neanderthals to the dispersal of H. sapiens in western Europe. We sequenced a twofold coverage mitochondrial genome from this bone, indicating the individual belongs to the Neanderthal lineage. The mitogenome clusters with other Neanderthal mitogenomes previously generated from the Russian Altai region. Alongside this, an analysis of the lithic corpus from both regions suggests that a wider Neanderthal dispersal, linked to the Micoquian stone tool industry, occurred after ~60,000 y ago. We assessed the paleoclimate connection (temperature and precipitation) between these locations and identified a high habitat suitability corridor along 55°N, suggesting that the long-distance movement of Neanderthals would have been facilitated by periods of favorable climate.